Avaliação da sustentabilidade unidades familiares de produção do Alto Rio Pacuí, Montes ClarosMG, por meio da metodologia APOIA-NovoRural - Dalton Rocha Pereira (2008)
The sustainability of three family production units (here named A, B and C), belonging to family farmers and located in the upper Pacuí River valley, in Montes Claros/MG, was assessed. These social actors develop respectively the following rural reference activities: typical rural restaurant, horticulture and confectionery/compotes. The Environmental Impact Assessment System of New Rural Activities (APOIA-NovoRural) was applied to theses properties. A bibliographical survey was carried out about the area of study and about the chosen theory: family farming, sustainable agriculture, sustainable rural development, new Brazilian rurality and indicators of sustainability, what made possible to know the theoretical framework concerning the theme. A participatory diagnosis named DiPAC (Diagnostico Participativo do Alto Pacuí) was applied to the involved area of study. It was verified that the three production units scored similar performances, having respectively the following Global Indexes of Activity Impact: 0.74; 0.72 and 0.70. The performance average was 0.70, which is a value higher than the utility baseline of indicators (0.70). Therefore, the investigated properties were considered to be sustainable. In spite of the satisfactory performance, some indicators have presented low utility values, and the indicators of the dimensions 'Landscape Ecology' and 'Management and Administration' are the ones that most require intervention. If mitigatory measures are not carried out to correct such performance, these low values may impair the sustainability of activities in these family production units in future.